Recuperação de beta-caroteno de óleo de palma bruto através de operações de adsorção e dessorção: estudos de cinética, equilíbrio e termodinâmica - Steffens, Bruna Clarissa (2023)
The palm oil is used in several industrial segments. During the palm oil refining process, minor compounds such as β-carotene, phytosterols, squalene and tocotrienols are lost due to the process conditions applied. Among these compounds, β-carotene has numerous applications due its antioxidant, pro-vitamin A activity and high commercial value. The present work evaluated the recovery of β-carotene from crude palm oil by adsorption and desorption strategy. The palm oil fractions from the adsorption operation were characterized for free fatty acid content, peroxide value, iodine value and melting point by differential scanning calorimetry (DSC). The analysis demonstrated the possibility of palm oil utilization for edible purposes after the adsorption step. Five synthetic polymer adsorbents were evaluated in batch mode: Diaion HP20, Sepabeads SP70, Sepabeads SP700, Diaion HP2MGL, Amberlite XAD7HP. The kinetics and adsorption equilibrium assays and thermodynamic parameters calculation were performed for Sepabeads SP70 resin, which revealed the highest adsorption capacity for β-carotene adsorption from palm oil micelle in isopropanol. The experimental data were best described by the pseudo-second-order kinetic model. The Weber and Morris kinetic model indicated that the mass transfer in the adsorption is a multiple steps phenomena. The Hill De Boer and Langmuir equilibrium models were able to describe the experimental data. The theoretical maximum adsorption capacity determined by the Langmuir model was 0.76 ± 0.03 mg.g-1. The thermodynamic parameters indicated a favorable, spontaneous and exothermic adsorption associated with physical bonding. Sequential cycles of adsorbent usage indicated the possibility of reusing the Sepabeads SP70 resin for, at least, 5 cycles based on the values of adsorption capacity. The possibility of adsorbent reutilization was verified by scanning electron microscopy (SEM) and Brunauer, Emmett and Teller (BET) method characterization. The desorption was evaluated in single stage and multiple stages using isopropanol and hexane sequentially. The enrichment factor increased from 1.85 ± 0.10 to 3.40 ± 0.21 when employing multiple stages. The present study showed that the recovery of β-carotene from crude palm oil is feasible. The recovery of βcarotene from palm oil contributes to the valorization of the palm oil production chain, since it recovers a bioactive compound that would be naturally degraded during the refining of this raw material.